Preparation of High-Performance Enteromorpha Prolifera–Based Porous Carbons by Nitrogen Modification and Their Electrochemical Performance - Li, Ming; Han, Kuihua; Teng, Zhaocai; Wang, Meimei; Cao, Yang; Li, Xian (Frontiers in Energy Research, 2021)
This study presents a novel method to improve the electrochemical performance of porous carbons (PCs) by simply adjusting the elemental composition of their precursors with nitrogen-rich materials as additives. Nitrogen modified enteromorpha prolifera-based (EP-based) PCs are prepared from EP and urea (or melamine). Overall, compared with the control PC without nitrogen modification, their pore structures and surface chemical properties present similar improvement. When used in supercapacitors, their significant development of mesopores at 2.5-7.0 nm can increase effective surfaces and promote ion migration. With an appropriate amount of nitrogen-containing or oxygen-containing functional groups maintaining surface wettability, the notable increase of graphitized N improves their conductivity. Due to the optimized pore structures and surface chemical properties, their specific capacitances increase by approximately 22%, their resistances are reduced, and they exhibit excellent high-rate capacitive performance and long cycle performance.